Adverse Outcomes Associated With Delaying or Withholding β-Blockers After Cardiac Surgery: A Retrospective Single-Center Cohort Study. (October 2020) - Chanan, Emily L.; Kendale, Samir M.; Cuff, Germaine; Galloway, Aubrey C.; Nunnally, Mark E.
Abstract : BACKGROUND: Ideal timing of postoperative β-blockers is unclear. We hypothesized that patients who do not receive β-blockers immediately after cardiac surgery would have increased in-hospital mortality (primary outcome) and postoperative hemodynamic, pulmonary, neurologic, or respiratory complications (secondary outcomes). METHODS: We performed a retrospective cohort study evaluating patients who underwent cardiac surgery at our institution from January 1, 2013 to September 30, 2017. We compared outcomes between patients who received β-blockers by postoperative day (POD) 5 with outcomes in patients who did not receive β-blockers at any time or received them after POD 5. Inverse probability of treatment weighting was used to minimize confounding. Univariate logistic regression analyses were performed on the weighted sets using absent or delayed β-blockers as the independent variable and each outcome as dependent variables in separate analyses. A secondary analysis was performed in patients prescribed preoperative β-blockers. E-values were calculated for significant outcomes. RESULTS: All results were confounder adjusted. Among patients presenting for cardiac surgery, not receiving β-blockers by POD 5 or at any time was not associated with the primary outcome in-hospital mortality, estimated odds ratio (OR; 99.5% confidence interval [CI]) of 1.6 (0.49–5.1), P = .28. Not receiving β-blockers by POD 5 or at any time was associated with postoperative atrial fibrillation, estimated OR (99.5% CI) of 1.5 (1.1–2.1), P < .001, and pulmonary complications, estimated OR (99.5% CI) of 3.0 (1.8–5.2), P < .001. E-values were 2.4 for postoperative atrial fibrillation and 5.6 for pulmonary complications. Among patients presenting for cardiac surgery taking preoperative β-blockers, not receiving β-blockers by POD 5 or at any time was not associated with the primary outcome mortality, with estimated OR (99.5% CI) of 1.3 (0.43–4.1), P = .63. In this subset, not receiving β-blockers by POD 5 or at any time was associated with increased adjusted ORs of postoperative atrial fibrillation (OR = 1.6; 99.5% CI, 1.1–2.4; P < .001) and postoperative pulmonary complications (OR = 2.8; 99.5% CI, 1.6–5.2; P < .001). Here, e-values were 2.7 for postoperative atrial fibrillation and 5.1 for pulmonary complications. For the sensitivity analyses for secondary outcomes, exposure and outcome periods overlap. Outcomes may have occurred before or after postoperative β-blocker administration. CONCLUSIONS: Among patients who undergo cardiac surgery, not receiving postoperative β-blockers within the first 5 days after cardiac surgery or at any time is not associated with in-hospital mortality and is associated with, but may not necessarily cause, postoperative atrial fibrillation and pulmonary complications.